2018
DOI: 10.3389/fmicb.2018.01000
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Nutrients and Bradyrhizobium japonicum on the Growth and Root Architecture of Soybean (Glycine max L.)

Abstract: Understanding the symbiotic performance of rhizobia and responses of plant root systems to mineral nutrient supply will facilitate the development of strategies to enhance effective rhizobia-legume symbioses. Interactive effect of nitrogen (N), phosphorus (P), and magnesium (Mg) on the symbiotic performance of soybean (Glycine max L.) with Bradyrhizobium japonicum, nodulation, root architecture, and the N concentration in plant tissue under hydroponic conditions were studied. Plant growth was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 55 publications
(62 reference statements)
4
31
0
1
Order By: Relevance
“…The ST-PGPR produce IAA which is required for cell division and elongation in plants coping with salt stress. Some of the best-known ST-PGPR producing IAA under salt stress are Azotobacter, Arthrobacter, Azospirillum, Pseudomonas, Stenotrophomonas, and Rahnella (Egamberdieva et al, 2008(Egamberdieva et al, , 2018Piccoli et al, 2011;Abd_Allah et al, 2017). Studies have confirmed that under salt stress yield loss in crops can be minimized by the application of phytohormone producing ST-PGPR.…”
Section: Plant Growth Regulatorsmentioning
confidence: 99%
“…The ST-PGPR produce IAA which is required for cell division and elongation in plants coping with salt stress. Some of the best-known ST-PGPR producing IAA under salt stress are Azotobacter, Arthrobacter, Azospirillum, Pseudomonas, Stenotrophomonas, and Rahnella (Egamberdieva et al, 2008(Egamberdieva et al, , 2018Piccoli et al, 2011;Abd_Allah et al, 2017). Studies have confirmed that under salt stress yield loss in crops can be minimized by the application of phytohormone producing ST-PGPR.…”
Section: Plant Growth Regulatorsmentioning
confidence: 99%
“…Endophytes are microorganisms that inhabit healthy plant tissues at specific growth stages, or whole stages of their life cycle, and establish a symbiotic relationship with the host without causing any apparent disease symptoms (Petrini, 1991;Duan et al, 2013;Castro et al, 2014;Egamberdieva et al, 2017bEgamberdieva et al, , 2018Li et al, 2018;Liu et al, 2019). Endophytic actinobacteria are considered to be a vital resource of microbial biodiversity (Matsumoto and Takahashi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high porosity of biochar may provide a habitat for microorganisms that can decompose the organic matter on the biochar surface [12]. Accordingly, biochar was used as an inoculant carrier to enhance the rhizobium survival rate and the soybean nodulation rate [13,14].…”
Section: Introductionmentioning
confidence: 99%